2022
DOI: 10.3390/polym14020302
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Salinized Nano ZrO2 Particles on the Microstructure, Hardness, and Wear Behavior of Acrylic Denture Tooth Nanocomposite

Abstract: The wear of acrylic denture teeth is a serious problem that can change the vertical dimensions of dentures. This study evaluates the effect of adding salinized nano ZrO2 particles on the microstructure, hardness, and wear resistance of acrylic denture teeth. Heat polymerizing polymethyl methacrylate resin was mixed with salinized ZrO2 at concentrations of 5 wt% and 10 wt%. Acrylic resin specimens without filler addition were used as a control group. SEM/EDS analyses were performed and the Vickers’ hardness was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 42 publications
2
13
0
Order By: Relevance
“…The reason is that the date-seed nanoparticles function as natural lubricants. This finding is in good agreement with the results reported in 46 .…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…The reason is that the date-seed nanoparticles function as natural lubricants. This finding is in good agreement with the results reported in 46 .…”
Section: Resultssupporting
confidence: 94%
“…Moreover, the total saturation of the examined composites may be justified by the fact that the normal load was transferred through the interfacial surfaces to the strongest material, namely, the nanoparticles 47 , 48 . Our results agree with those of Shirkavand et al 46 , who found that the PMMA compressive strength increased as the resin strength increased with increasing filler weight. As illustrated in Fig.…”
Section: Resultssupporting
confidence: 93%
“…ZrO 2 is a biocompatible metal dioxide with high strength, fracture toughness, and surface hardness [ 21 , 22 ]. Moreover, ZrO 2 has resistance to corrosion [ 23 ], thermal stability [ 24 ], and antibacterial and antifungal effects on C. albicans and Aspergillus niger [ 25 ]. Several studies found that incorporating specific concentrations of ZrO 2 NPs into PMMA increased the surface hardness, flexure strength, impact strength, and fracture toughness of the resin and enhanced it [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…ZrO 2 NPs have been demonstrated as a suitable reinforcing material for 3D-printed PMMA [ 53 ]. Furthermore, ZrO 2 has thermal stability, corrosion resistance, and antibacterial and antifungal effects on Aspergillus niger and C. albicans [ 39 , 54 , 55 ]. Reinforcing PMMA with ZrO 2 NPs can endure denture base resins with the favorable characteristics of ZrO 2 [ 18 ].…”
Section: Discussionmentioning
confidence: 99%